PF4/heparin complexes are T cell–dependent antigens - Suvarna, Shayela (The American Society of Hematology, 2005)
Heparin-induced thrombocytopenia (HIT) is a life-threatening, thrombotic disorder associated with development of anti–platelet factor 4 (anti-PF4)/heparin autoantibodies. Little is known about the antigenic and cellular requirements that initiate the immune response to these complexes. To begin to delineate mechanisms of autoantibody formation in HIT, we studied the immunizing effects of murine PF4 (mPF4)/heparin in mice with and without thymic function. Euthymic mice were injected with mPF4/heparin complexes, mPF4, heparin, or buffer. Mice injected with mPF4/heparin, but not mPF4 or heparin alone, developed heparin-dependent autoantibodies that shared serologic and functional characteristics of human HIT antibodies, including preferential binding to mPF4/heparin complexes and causing heparin- and FcRγIIA-dependent platelet activation. In contrast, athymic mice did not develop HIT-like antibodies. Taken together, these studies establish that PF4/heparin complexes are highly immunogenic and elicit self-reacting anti-PF4/heparin antibodies in a T cell–dependent manner.